2010
DOI: 10.1007/s10832-010-9622-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preheating process on crystallization and optical properties of sol-gel derived ZnO semiconductor thin films

Abstract: Highly transparent ZnO semiconductor thin films were deposited onto alkali-free glass substrates by a sol-gel spin coating process. This research investigated the effects of different preheating rates (4 or 10°C/min) on the various surface morphologies, crystallization characteristics, and optical properties of these thin films. The ZnO sol was synthesized by dissolving the zinc acetate dihydrate in isopropanol (IPA), and then adding monoethanolamine (MEA). These as-coated films were preheated at 300°C for 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…As noted above, we collected a large number of published Tauc analyses of undoped ZnO that included plots of the absorbance data against the photon energy . This was critical, as our assessment of the application of the Tauc method required the consistent application of a fitting method, as described below.…”
Section: Modelmentioning
confidence: 99%
“…As noted above, we collected a large number of published Tauc analyses of undoped ZnO that included plots of the absorbance data against the photon energy . This was critical, as our assessment of the application of the Tauc method required the consistent application of a fitting method, as described below.…”
Section: Modelmentioning
confidence: 99%
“…The process of formation of polycrystalline thin films by sol-gel processing involves three steps: solvent evaporation, precursor decomposition and crystallization. Various factors that affect the structure of these films are pre-firing temperature, composition, firing or annealing temperature, and rate of heating [40][41][42][43]. Ohyama et al [43] reported that low heating rates result in dense ZnO films, because the film is given enough time for structural relaxation before crystallization.…”
Section: Mechanism Of Growth Of Mg X Zn 1−x O Nanocrystalline Thin Filmsmentioning
confidence: 99%
“…This material is currently considered a semiconductor synthesized through a process of new techniques, where growth brings new physical properties, as well as technological applications [7][8][9][10]. Zinc oxide has different electronegativities of zinc and oxygen, and the most stable crystalline structure is the hexagonal wurzite type [11][12][13][14]. Zinc oxide has technological interest and especially in nanometer-level structures, because it is possible to obtain nanostructures in the form of nanoparticles, where different structures are observed in both form and type, generating various nanostructures in the form of nanoparticles, nanowires, nanofiber, as the main ones.…”
Section: Introductionmentioning
confidence: 99%